2017
DOI: 10.1021/acs.jafc.7b04149
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic Changes during Storage of Brassica napus Seeds under Moist Conditions and the Consequences for the Sensory Quality of the Resulting Virgin Oil

Abstract: Virgin rapeseed (Brassica napus) oil is a valuable niche product, if delivered with a high quality. In this study, the effects of moist storage of B. napus seeds for 1 to 4 days on the seed metabolome and the chemo-sensory properties of the produced oils were determined. The concentrations of several primary metabolites, including monosaccharides and amino acids, rapidly increased in the seeds, probably indicating the breakdown of storage compounds to support seed germination. Seed concentrations of indole glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…If the raw materials are rancid and deteriorated and contain molds, then they cannot be used in edible oil production. It has been reported that with the prolongation of storage time, the quality and yield of oil from the seeds was decreased (Bonte et al, 2017;Han et al, 2017).…”
Section: Risks During Harvesting and Post-harvestmentioning
confidence: 99%
“…If the raw materials are rancid and deteriorated and contain molds, then they cannot be used in edible oil production. It has been reported that with the prolongation of storage time, the quality and yield of oil from the seeds was decreased (Bonte et al, 2017;Han et al, 2017).…”
Section: Risks During Harvesting and Post-harvestmentioning
confidence: 99%
“…During the last decade, growing interest in the use of different plant parts of O. ficus-indica arose, resulting in a large number of scientific papers on the composition of the flowers, fruits, and seeds [ 5 , 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. To the best of our knowledge, all these studies dealt with seeds and fruits of prickly pear, but only few studies took cactus seed oil into account [ 6 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds were also found in virgin rapeseed oil especially when the raw material has been stored under moist conditions. With increasing storage time, the amount of the aldehydes in the resulting oil increased significantly [20]. Acetaldehyde is produced by partial oxidation of ethanol resulting from the metabolization of carbohydrates by yeasts.…”
Section: Volatile Compounds Of Cactus Seed Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional abbreviations are given in the top right box. (b) is based on the metabolic map designed by R. Schweiger [37,38].…”
Section: C:n Ratio Amino Acids and Glucosinolates In The Leaves Of Pl...mentioning
confidence: 99%